Study of orientation effects to pool boiling heat transfer performance from the circular pin fins structure - Yasirul Khoiri; Indro Pranoto; Muhammad Aulia Rahman (TEKNOSAINS : Jurnal Sains, Teknologi dan Informatika, 2024)
Increasingly sophisticated technological advances generate heat that needs to be managed properly to ensure the optimality of the operation of these components. One solution offered is the pool boiling cooling method, which has a high heat transfer coefficient. This research aims to study how the orientation angle of the boiling pool affects the heat transfer coefficient. This approach aims to improve cooling effectiveness, especially in the context of moving systems, where the influence of orientation angle is an important factor. In the research related to pool boiling, various orientation angles from 0° to 20° were used on aluminum-based fins in the form of inline pin fins. These fins have a circular shape with a size of 30 mm × 30 mm. The working fluid used in this study is HFE-7100, which has dielectric properties. This study was conducted with heat levels ranging from 10 to 50 W before reaching the Critical Heat Flux (CHF) value. The results show that the orientation angle has a significant impact on the heat transfer coefficient as well as the dynamics of bubble formation. The results also indicate that the greater the orientation angle, the smaller the area of spread and bubble growth that occurs. This decrease in bubble growth area results in an increase in surface temperature. With the circular pin fins test specimen, an increase in surface temperature was found in this study, when the angle θ = 10° amounted to 1.08℃, for the angle θ = 20° amounted to 2.37℃ under the condition of q'' = 55.56 kW/m2. While the highest average value of heat transfer coefficient  occurs at angle θ = 0°, the value  reaches 3.91 kW/m2∙K and decreases at angle θ = 10° by 3.79%, for angle θ = 20° by 6.56%